Identification of anti‐CD98 antibody mimotopes for inducing antibodies with antitumor activity by mimotope immunization. Issue 4 (17th March 2014) - Saito, Misa; Kondo, Masahiro; Ohshima, Motohiro; Deguchi, Kazuki; Hayashi, Hideki; Inoue, Kazuyuki; Tsuji, Daiki; Masuko, Takashi; Itoh, Kunihiko
<x xml:space="preserve">Abstract</x> A mimotope is an antibody‐epitope‐mimicking peptide retrieved from a phage display random peptide library. Immunization with antitumor antibody‐derived mimotopes is promising for inducing antitumor immunity in hosts. In this study, we isolated linear and constrained mimotopes from HBJ127, a tumor‐suppressing anti‐CD98 heavy chain mAb, and determined their abilities for induction of antitumor activity equal to that of the parent antibody. We detected elevated levels of antipeptide responses, but failed to detect reactivity against native CD98‐expressing HeLa cells in sera of immunized mice. Phage display panning and selection of mimotope‐immunized mouse spleen‐derived antibody Fab library showed that HeLa cell‐reactive Fabs were successfully retrieved from the library. This finding indicates that native antigen‐reactive Fab clones represented an undetectable minor population in mimotope‐induced antibody repertoire. Functional and structural analysis of retrieved Fab clones revealed that they were almost identical to the parent antibody. From these results, we confirmed that mimotope immunization was promising for retrieving antitumor antibodies equivalent to the parent antibody, although the co‐administration of adjuvant compounds such as T‐cell epitope peptides and Toll‐like receptor 4 agonist peptides is likely to be necessary for inducing stronger antitumor immunity than mimotope injection alone.